Organic Salts of Pharmaceutical Impurity p-Aminophenol - Khandavilli, U B Rao; Keshavarz, Leila; Skořepová, Eliška; Steendam, René R E; Frawley, Patrick J (Molecules (Basel, Switzerland), 2020)
The presence of impurities can drastically affect the efficacy and safety of pharmaceutical entities. p-Aminophenol (PAP) is one of the main impurities of paracetamol (PA) that can potentially show toxic effects such as maternal toxicity and nephrotoxicity. The removal of PAP from PA is challenging and difficult to achieve through regular crystallization approaches. In this regard, we report four new salts of PAP with salicylic acid (SA), oxalic acid (OX), l-tartaric acid (TA), and (1S)-(+)-10-camphorsulfonic acid (CSA). All the PAP salts were analyzed using single-crystal X-ray diffraction, powder X-ray diffraction, infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analysis. The presence of minute amounts of PAP in paracetamol solids gives a dark color to the product that was difficult to remove through crystallization. In our study, we found that the addition of small quantities of the aforementioned acids helps to remove PAP from PA during the filtration and washings. This shows that salt formation could be used to efficiently remove challenging impurities.
Keywords: Organic Chemicals; aminofenoly; prášky, zásypy, pudry; Powders; impurity removal; Molecular Structure; 4-aminophenol or p-aminophenol; Pharmaceutical Preparations; Aminophenols; krystalografie rentgenová; léčivé přípravky; Models, Molecular; particle size; molekulární struktura; Salts; molekulární modely; paracetamol; salt; organické látky; Drug Contamination; soli; Crystallography, X-Ray; kontaminace léku